Get Answers to all your Questions

header-bg qa

q4) Factorise 

iv)

x ^ 4 - ( x-z ) ^ 4

Answers (1)

best_answer

We have,
              x ^ 4 - ( x-z ) ^ 4  = (x^{2})^{2} - ((x-z)^{2})^{2}                                       using \ a^{2}-b^{2} = (a-b)(a+b)
                                             =(x^{2} - (x-z)^{2})(x^{2}+(x-z)^{2})
                                             = (x+(x-z))(x - (x-z))(x^{2}+(x-z)^{2})
                                             =(2x - z)(z)(x^{2}+(x-z)^{2})
 

Posted by

Gautam harsolia

View full answer